Marketinški diskurz - Huš, Katja (Družboslovne razprave, 2011)
The article presents a Foucauldian archaeologico-genealogical analysis of the constitution of the marketing discipline in the post-war USA (1945-1974). The marketing concept that defined the specifics of marketing with the idea of placing the recognition and satisfaction of the consumer, his/her needs, wishes and demands at the beginning of the production process and which emerged as the discipline's main theoretical concept is presented as a statement, the consumer as its derivative and the newly formed object of marketing discourse. The article then presents some historical conditions of possibility of the emergence of the marketing concept. The article finds that the Keynesian political economy and its implementation in the state's economic policy, along with development of the market research field, the birth of consumer rights, extensive legislation that addressed consumer protection and institutions of the new wave of consumer movement presumed the existence of the consumer as a specific entity, creating him/ her as an ever more important, specific and natural politico-economic category and point of identification and thus functioned to provide the historical conditions of such a possibility, creating a space within which the marketing concept could emerge.
Keywords: Marketing; Trženje; Discourse; Diskurz; Consumption; Potrošnja; Consumers; Potrošniki; United States of America; ZDA